2016
DOI: 10.11005/jbm.2016.23.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Fractures in Patient with Graves' Disease Accompanied by Isolated Hypogonadotropic Hypogonadism

Abstract: Isolated hypogonadotropic hypogonadism (IHH) is known to decrease bone mineral density due to deficiency of sex steroid hormone. Graves' disease is also an important cause of secondary osteoporosis. However, IHH does not preclude the development of primary hyperthyroidism caused by Graves' disease, leading to more severe osteoporosis rapidly. Here, we describe the first case of 35-year-old Asian female patient with IHH accompanied by Graves' disease and osteoporosis-induced multiple fractures. Endocrine labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Of note, in this study, compared with the control group, it was demonstrated that the levels of FT3, FT4, TT3 and TT4 in the observation group were significantly increased, with significantly decreasing level of TSH, indicating that the thyroid function in patients with hyperthyroidism was abnormally enhanced. Moreover, the BMD in the observation group was significantly lower than that in the control group, which was in line with previous findings (14,15), indicating that in the case of excessive secretion of thyroid hormone, both the BMD and osteogenic function in the body are impaired. Importantly, in the observation group, the level of inflammatory factor IL-2 was significantly lower than that in the control group, while the levels of IL-6 and TGF-β were significantly higher, suggesting that the immune function of patients with hyperthyroidism is inhibited.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of note, in this study, compared with the control group, it was demonstrated that the levels of FT3, FT4, TT3 and TT4 in the observation group were significantly increased, with significantly decreasing level of TSH, indicating that the thyroid function in patients with hyperthyroidism was abnormally enhanced. Moreover, the BMD in the observation group was significantly lower than that in the control group, which was in line with previous findings (14,15), indicating that in the case of excessive secretion of thyroid hormone, both the BMD and osteogenic function in the body are impaired. Importantly, in the observation group, the level of inflammatory factor IL-2 was significantly lower than that in the control group, while the levels of IL-6 and TGF-β were significantly higher, suggesting that the immune function of patients with hyperthyroidism is inhibited.…”
Section: Discussionsupporting
confidence: 92%
“…Hyperthyroidism is characterized as an endocrine disorder, which results in abnormality of hormone secretion and triggers various complications (13). In clinical practice, abnormal bone metabolism is found in patients with hyperthyroidism, and a majority of cases are accompanied with osteoporosis, thus it is proposed that hyperthyroidism is associated with bone mineral density (BMD) (14,15). In addition, hyperthyroidism is an autoimmune disease, and the immune function is impaired with abnormal secretion of inflammatory factors (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…2 In addition, some diseases such as kidney diseases, endocrinal diseases, and anorexia may result in osteoporosis. 3,4…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition, some diseases such as kidney diseases, endocrinal diseases, and anorexia may result in osteoporosis. 3,4 Clostridium botulinum bacteria is the source of production of botulinum toxin (BTX). It has seven toxin subtypes (A, B, C1, D, E, F, and G).…”
Section: Introductionmentioning
confidence: 99%